KUALITAS PENGASUHAN DAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU SEKSUAL REMAJA - Utami, Shanti; Ekasari, Agustina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
This study aims to determine the relationship and influence the quality of care and the intensity of the use of social media to the sexual behavior of high school adolescents Bekasi city. This research uses quantitative method with Cross Sectional Survey research design. Subjects in this study were students of high school and SMK class X and XI in Bekasi district, amounting to 536 students. This study used parenting quality scale with reliability value of Alpha Cronbach 0,920, and scale of social media use intensity with reliability value of Alpha Cronbach 0,897 and scale of sexual behavior with reliability value of Alpha Cornbach 0,912. Technique of data analysis using Rank-Spearman correlation. This study found that there is no relationship between the quality of care with high school adolescent sexual behavior. However, there is an influence that the intensity of social media use affects the sexual behavior of high school adolescents